Respuesta :

Answer:

B. None

Step-by-step explanation:

We can use substitution for this.

First solve the first equation for y:

y + 7x = -3

y = -7x - 3

Now, substitute this expression in for y in the second equation:

14x + 2(-7x - 3) = 6

We can then solve for x:

14x - 14x - 6 = 6

0 - 6 = 6

-6 = 6

However, we know that -6 ≠ 6, so there are no solutions to this system. Thus, the answer is B, none.

Hope this helps!

Answer:

no solutions

Step-by-step explanation:

y+7x =-3

14x+2y = 6

Multiply the first equation by -2 to eliminate x and y

-2y-14x = 6

14x+2y = 6

--------------------------

0 = 12

This is never true, so there are no solutions